The Role of Inspiring Leadership in Promoting Innovative Thinking among Employees: A Field Study on Misr Insurance - Eid, Samah (The Arab Journal of Administration, 2023)
This modern research deals with inspiring leadership as the main pillar for improving the performance of employees by enhancing their innovative thinking, which contributes to improving the organizational performance of organizations in general and those working in the field of insurance in particular. The importance of this is due to the fact that the human element has become in the light of the competitive economy and the era of informatics, it is the real capital of organizations as it is the corner that plays the main role in the process of innovation and renewal, and it is the leader in the process of change and creativity, especially in the field of insurance, and thus is able to transform knowledge into Value and then to a competitive advantage, which means that the center of gravity in generating value has shifted from the exploitation of natural (physical) resources to the exploitation of intellectual assets (intangible), and from the law of diminishing returns (which applies to physical goods) to the law of increasing returns (regarding It is related to knowledge and innovation) and this is what the Egyptian insurance sector needs.